2022
DOI: 10.3389/fneur.2022.792295
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Gaps in Biophysical Changes After Powered Robotic Exoskeleton Walking by Individuals With Spinal Cord Injury—A Scoping Review

Abstract: In addition to helping individuals with spinal cord injury (SCI) regain the ability to ambulate, the rapidly evolving capabilities of robotic exoskeletons provide an array of secondary biophysical benefits which can reduce the complications resulting from prolonged immobilization. The proposed benefits of increased life-long over-ground walking capacity include improved upper body muscular fitness, improved circulatory response, improved bowel movement regularity, and reduced pain and spasticity. Beyond the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Furthermore, with the popularization of exoskeleton technology—both for rehabilitation and for personal use, this trend may change in the foreseeable future when advanced technology becomes more ubiquitously available. Yip et al showed in a robust scoping review that there are numerous benefits to upright over-ground walking for chronic SCI individuals ( 28 ). These secondary biophysical benefits may also entice physicians and SCI individuals to adopt more walking exercises as a means to achieve life-long health maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the popularization of exoskeleton technology—both for rehabilitation and for personal use, this trend may change in the foreseeable future when advanced technology becomes more ubiquitously available. Yip et al showed in a robust scoping review that there are numerous benefits to upright over-ground walking for chronic SCI individuals ( 28 ). These secondary biophysical benefits may also entice physicians and SCI individuals to adopt more walking exercises as a means to achieve life-long health maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, we have seen significant scientific breakthrough in the arena of assistive technology and robotics in rehabilitation ( 26 28 ). Literature on innovative rehabilitation technology such as virtual reality has shown that it was useful in reducing neuropathic pain ( 29 ), enhancing rehabilitation of upper limb function ( 30 ), balance, motor recovery, as well as helping to improve user morale and participation among individuals with SCI ( 31 ).…”
Section: Introductionmentioning
confidence: 99%